Identification and Management of CKD-Associated Pruritus: Current Insights - Skrzypczak T; Skrzypczak A; Nockowski P; Szepietowski JC (International Journal of Nephrology and Renovascular Disease, 2024)
Tomasz Skrzypczak,1 Anna Skrzypczak,2 Piotr Nockowski,3,4 Jacek C Szepietowski3,4 1University Hospital in Wroclaw, Wroclaw, 50-556, Poland; 2Citodent Dental Clinic, Wroclaw, 50-457, Poland; 3Department of Dermato-Venereology, 4th Military Hospital, Wroclaw, 53-114, Poland; 4Faculty of Medicine, Wroclaw University of Science and Technology, Wroclaw, 51-377, PolandCorrespondence: Jacek C Szepietowski, Faculty of Medicine, Wroclaw University of Science and Technology, Grunwaldzki sq. 11, Wroclaw, 51-377, Poland, Email jacek.szepietowski@pwr.edu.plAbstract: Chronic kidney disease-associated pruritus (CKD-aP) is a frequent and distressing problem for individuals with chronic kidney disease (CKD) and end-stage renal disease. It affects around 20% of those with CKD and 40% of those with end-stage renal disease. Despite its clear association with poorer psychosocial and medical outcomes, it is often underreported by patients and frequently remains unnoticed by healthcare providers. This is likely due to uncertainty regarding its diagnosis and treatment. Most commonly, CKD-aP could be screened with questionnaires like the KDQoL-36 and WI-NRS, chosen for their simplicity and ease of use. Prior treatment studies of CKD-aP were mostly limited by noncontrolled design and small sample size. First CKD-aP medication – difelikefalin a powerful, new therapeutic option was approved by Federal Drug Administration (FDA) in 2021 and European Medicines Agency (EMA) in 2022. Recent expert opinions, clinical trials and metanalysis identified difelikefalin and gabapentinoids as medications of choice in treatment of CKD-aP. All these findings improved current understanding and management of this condition.Keywords: difelikefalin, chronic kidney disease, itch, pruritus, pregabalin, gabapentin